THE SOROGAN VERSION OF ACADEMIC MOTIVATION SCALE (AMS-VS) FOR ISLAMIC BOARDING SCHOOL STUDENTS - Maba, Aprezo Pardodi; Pratiwi, Betty Dwi; Cahyani, Anugrah Intan; Yusuf, Muhammad (Faculty of Psychology, Diponegoro University, 2020)
There are many instruments that have been developed by researchers to measure motivation. However, none of the instruments has been specifically designed to measure sorogan motivation on Islamic boarding school students (santri). Therefore, this article was written to discuss the processes of adaptation, testing the validity, and reliability of academic motivation scales to measure sorogan motivation of santri. The authors use Theory of Self Determination (Deci & Ryan, 1995), Academic Motivation Scale (Vallerand et al., 1992), and AMS Bahasa Indonesia (Natalya & Purwanto, 2018) as guidelines in compiling indicators, aspects, and items of Academic Motivation Scale Sorogan Version (AMS-VS). Test adaptation guidelines issued by the International Test Commission (2018) are used in adapting the AMS. The data collected from 102 respondents were analysed using Confirmatory Factor Analysis (CFA). The results showed that AMS-VS is a proper and strong measurement to determine the level sorogan motivation of santri.